In vitro fatigue test on artificial heart devices - TAKAMURA, K.; MASHIMO, I.; WASHIZU, T.; WAKAI, H.; KATO, K.; MOCHIZUKI, T.; NAKAGAKI, M.; KATO, E.; TAGUCHI, K.; MORIFUJI, K.; MATSUMURA, H.; SUMA, T. (Jinko Zoki, 1974)
Strength and fatigue tests were extracorporeally performed on silicone rubber, one of the materials of the artificial heart device pump, and the following results were obtained. 1) It is necessary to sandwich two mesh sheets between the silicone rubber membranes and to limit the directional expansion and contraction to a minimum level. 2) The connection between the housing and chamber was found to have sufficient strength through motion model tests performed 10 million times. In the fatigue test, fatigue associated with frequency of motion could not be demonstrated.